2019
DOI: 10.3389/fimmu.2019.02487
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB RelA Transcription Factor Is Critical for Regulatory T Cell Activation and Stability

Abstract: Regulatory T cells (Tregs) play a major role in immune homeostasis and in the prevention of autoimmune diseases. It has been shown that c-Rel is critical in Treg thymic differentiation, but little is known on the role of NF-κB on mature Treg biology. We thus generated mice with a specific knockout of RelA, a key member of NF-κB, in Tregs. These mice developed a severe autoimmune syndrome with multi-organ immune infiltration and high activation of lymphoid and myeloid cells. Phenotypic and transcriptomic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…It has been demonstrated that TNFR family co-stimulation increases regulatory T cell activation and function via NF-κB [ 62 ]. Moreover, it was shown that the NF-κB RelA subunit (p65) transcription factor is critical for T reg activation and stability [ 63 ]. This could explain why TNFR2 KO-MSCs maintain a certain level of immunoregulation and are still able to induce T regs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that TNFR family co-stimulation increases regulatory T cell activation and function via NF-κB [ 62 ]. Moreover, it was shown that the NF-κB RelA subunit (p65) transcription factor is critical for T reg activation and stability [ 63 ]. This could explain why TNFR2 KO-MSCs maintain a certain level of immunoregulation and are still able to induce T regs.…”
Section: Discussionmentioning
confidence: 99%
“…Foxp3‐CRE‐IRES‐YFP ( Foxp3 Cre ) [50] and Foxp3‐IRES‐GFP [51] ( Foxp3 GFP ) knock‐in mice were kindly given by Prs. Alexander Rudensky and Bernard Malissen, respectively, and Rela flox knock‐in mice were previously described [52]. Foxp3‐DTR ( Foxp3 tm3(DTR/GFP)Ayr/J ), Tnf −/− ( Tnf tm1Gk1/J ), and Tnfrsf1b −/− ( Tnfrsf1 btm1Mwm/J ) were obtained from the Jackson laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…RelA‐deficient Tregs and their control Tregs were similarly purified from Foxp3 Cre/+ x Rela flox and Foxp3 Cre/+ mice, respectively. We used Foxp3 Cre/+ x Rela flox mice because they did not develop autoimmunity, contrary to Foxp3 Cre x Rela flox mice as we recently reported [52].…”
Section: Methodsmentioning
confidence: 99%
“…76 It is demonstrated that TNFR family co-stimulation increases Treg activation and function via NF-κB. 77,78 This could explain why priming ECFCs with 1 ng/ml of TNFα could still increase ECFC immunoregulatory effect. Apparently, this cross talk might be in an undemocratic manner since TNFR2 seems to govern the nal fate of TNFα signaling cascade.…”
Section: Several Studies Reported That Immunosuppressive Effect Of Vementioning
confidence: 99%